In want of a viscount - Heath, Lorraine (Heath, Lorraine. Chessmen: masters of seduction, 2024)
"American Leonora Garrison has come to England in desperate search of investors to keep her family business afloat but instead finds surprising pleasure when she visits an exclusive ladies' club and dares to kiss a stranger, who leaves her yearning for more. With a libertine for a father, Viscount Wyeth, more commonly known as Rook, vowed to live his life above reproach, with nary a hint of disgrace. Until one night, he takes a mysterious beauty into his arms, a lady who tempts him to cast his sterling reputation aside in favor of more wicked pursuits. When fate reunites the couple, they are torn between desire and duty. Leonora may want the viscount, but she needs a stakeholder not a lover. When caught in a compromising situation that places everything they hold dear at risk, they must determine how best to win. However, in this scandalous game, nothing except love takes all."--